Investigation of the flexural and thermomechanical properties of nanoclay/graphene reinforced carbon fiber epoxy composites. Issue 21 (14th November 2019) - Tareq, Md Sarower; Zainuddin, S.; Woodside, E.; Syed, F.
Abstract: Abstract : Flexural and thermomechanical properties of the epoxy-based carbon fiber composites (CFCs) on addition of single and binary nanoparticles (nanoclay and graphene) have been investigated. It was found that nanoclay acts more effectively in increasing the stiffness of the CFCs, whereas graphene is more effective in achieving higher strength. Nanoclay-added samples exhibited highest flexural (64.5 GPa) and storage (25.3 GPa) modulus among all types. Graphene-added samples showed highest improvement (by 21%) in flexural strength and exhibited most stable thermomechanical properties with highest energy dissipation capability (3.1 GPa loss modulus) in flexural test and dynamic mechanical analysis (DMA), respectively. By contrast, addition of binary nanoparticles reduced the stiffness and significantly increased the strain to failure (42%) of the composites. Optical microscopy and scanning electron microscopy indicated that addition of nanoparticles significantly reduced delamination and matrix cracking of the CFCs because of strong interfacial bonding and toughened matrix, respectively.